Effect of dietary orange peel essential oil on physiological, biochemical and metabolic responses of Japanese quails as affected by early age thermal conditioning and fasting - Dalkılıç, Bestami; Şimşek, Ülkü Gülcihan; Çiftçi, Mehmet; Baykalır, Yasin (My University, 2015)
Yüksek ortam sıcaklığı için en önemli sorunlardan biri olan dünyanın birçok bölgesinde kanatlı üretimi. Isı iklimlendirme nedeniyle ekonomik kayıplar için birçok kanatlı türlerinde yaşanmaktadır Isı stresi. Bu nedenle, portakal kabuğu esansiyel yağı etkisi (OEO) diyet oruç kısa vadeli telafi edici büyüme parametreleri üzerindeki takviyesi ve erken yaşta termal şartlandırılmış bıldırcın civciv çalışılmıştır. 168 sevenday- Eski bıldırcın civciv rastgele, kontrol olarak altı gruba ayrıldı sıcaklık ayarlama (36 ° ± 1 ° C ve 24 saat süreyle% 70-80 bağıl nem) ve açlık grubu (24 saat boyunca yem çekilmesi). Her bir grup ikiye bölünmüş ve alınan bir bazal yem veya 300 ppm OEO ile aynı bazal yem yem desteklenmiştir. Erken yaşta Termal klima ve oruç anlamlı büyüme sonuçlandı Deneyin 7-14 d arasındaki geriliği. Uçucu yağ tamamlayabilir olumlu etkilemiştir kilo ve bıldırcınların yem dönüşüm oranı en Benzer yem alımı ile 7-42, d. Temel ile erken yaşta termal meydan Yağ takviyesi ise meme yüzdesi arttı uyluk ve bel-boyun yüzdesi azalmıştır. Erken yaşta Termal klima daha boyunca ısı stresi ile başa çıkmak için daha iyi kapasite gösterdi Termal olmayan bıldırcın karşılaştırıldığında serum T3 düzeylerinde azalma klimalı. Bu sonuçlar, termal klima için erken maruz kalma önermek olabilir değiştirerek sonradan ısı yükü ile başa çıkmak için bıldırcın yeteneğini teşvik termoregülatuar fizyolojik yanıtlar. OEO takviyesi termotoleransı ediniminde iyi gelişmeler gösterdi. Içinde Sonuç, OEO takviyesi doğal büyüme hızlandırıcı olarak kullanılabilir Ya erken yaşta tedavi veya normal üreme civcivler.

High ambient temperature is one of the most important problems for poultry production in many regions of the world. Heat acclimatization has been experienced in many poultry species for economic losses due to heat stress. Therefore, the effect of orange peel essential oil (OEO) dietary supplementation on compensatory growth parameters of short-term fasted and thermal conditioned quail chicks at an early age was studied. 168 sevenday- old quail chicks were randomly assigned to six groups as the control, thermal conditioning (36°±1°C and 70-80 % RH for 24 h) and fasting group (feed withdrawal for 24 h). Each group was split into two and received a basal feed or the same basal feed with 300 ppm OEO supplemented feed. Thermal conditioning and fasting at early age significantly resulted in growth retardation between 7-14 d of the experiment. Essential oil supplementing positively influenced weight gain and feed conversion ratio of the quails at 7-42 d with similar feed intake. Early age thermal challenge with essential oil supplementation increased the breast percentage whereas thigh and waist-neck percentage was decreased. Thermal conditioning at early age demonstrated better capacity to cope with heat stress through greater reduction in serum T3 levels compared to quails that were not thermal conditioned. These results suggest that early exposure to thermal conditioning may promote quails’ ability to cope with the subsequent heat load by altering thermoregulatory physiological responses. OEO supplementation demonstrated the best improvements in thermotolerance acquisition. In conclusion, OEO supplementation can be used as a natural growth promoter either early age treated or normal breeding chicks.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Japanese quails; Orange peel essential oil; Thermotolerance; Growth performance; Biochemical parameters